2022
DOI: 10.3390/ijerph19053003
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Behavioral Therapy-Based Comprehensive Self-Management Program Improves Presenteeism in Persons with Irritable Bowel Syndrome: A Secondary Data Analysis

Abstract: Individuals with irritable bowel syndrome (IBS) are more likely to miss work (absenteeism), have reduced work effectiveness (presenteeism) and experience activity impairment. This study compared the effect of a comprehensive self-management (CSM) intervention program (incorporating cognitive behavioral therapy, diet education and relaxation) versus usual care on work- and activity-impairments in adults with IBS. This secondary data analysis used daily diaries and Work Productivity and Activity Impairment in Ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…For dietary treatment, IBS patients with diarrhea who were randomized to a low-fermentable oligo-, di-, and monosaccharide and polyol (FODMAP) diet showed a greater reduction in activity impairment after a 28-day intervention [ 42 ]. A comprehensive self-management program, including cognitive-behavioral therapy, dietary education, and relaxation, was effective in improving presenteeism, overall work productivity, and activity impairment, particularly among those with greater baseline work/activity impairment [ 43 ]. These results suggest that improving the abdominal symptoms of IBS and associated psychological problems may increase work productivity, as well as improve quality of life and health related economic problems.…”
Section: Effect Of Treatments For Ibs On Workmentioning
confidence: 99%
See 1 more Smart Citation
“…For dietary treatment, IBS patients with diarrhea who were randomized to a low-fermentable oligo-, di-, and monosaccharide and polyol (FODMAP) diet showed a greater reduction in activity impairment after a 28-day intervention [ 42 ]. A comprehensive self-management program, including cognitive-behavioral therapy, dietary education, and relaxation, was effective in improving presenteeism, overall work productivity, and activity impairment, particularly among those with greater baseline work/activity impairment [ 43 ]. These results suggest that improving the abdominal symptoms of IBS and associated psychological problems may increase work productivity, as well as improve quality of life and health related economic problems.…”
Section: Effect Of Treatments For Ibs On Workmentioning
confidence: 99%
“…3) Activity impairment was reduced with the low-FODMAP diet compared with the mNICE diet. Yang et al (2022) [ 43 ] United States Rome II A prospective, randomized, single-blind, controlled trial 160 IBS patients (Workers or students were 79.7% of the participants.) Participants were divided into 2 groups; one with a comprehensive self-management (CSM) intervention program (including CBT, dietary education, and relaxation) for work and activity impairment and a usual care group.…”
Section: Effect Of Treatments For Ibs On Workmentioning
confidence: 99%
“…For example, it has previously been shown that cognitive behavioral therapy‐based comprehensive self‐management for IBS was superior to usual care in improving overall work productivity loss and activity impairment with sustained effects up to 12 months. Such intervention was found to be particularly beneficial for IBS patients with greater baseline work and activity impairments 9 . The application of such approaches as part of IBS management strategies will not only benefit patients but also employers in order to reduce indirect costs associated with presenteeism.…”
Section: Study Population Absenteeism Presenteeismmentioning
confidence: 99%
“… 6 , 7 , 13 , 14 The association between IBS and shift work has been previously reported, and some meta-analyses indicate a higher prevalence of IBS among shift workers. 12 , 15 Various treatments for IBS, such as medication 16 and self-management programs, including CBT, 17 can improve the work productivity of individuals with IBS.…”
Section: Introductionmentioning
confidence: 99%